Effects of microstructure characteristics on the transverse moisture diffusivity of unidirectional composite - Wang Meng; Hang Xiaochen (Science and Engineering of Composite Materials, 2023)
To reveal the effects of the microstructure characteristics including fiber shape, void, fiber distribution pattern, and interphase on the transverse moisture diffusivities of unidirectional composites, the steady analysis method based on Fick’s law is adopted. The predicted numerical results are compared with the results from the analytical models to demonstrate the accuracy. From the simulation results, it is found that the increase in the oscillation amplification of non-circular fibers contributes to the orthotropy of diffusivity properties, which attributes to different barrier effects along different directions. The consideration of interphase relieves the barrier effects and the predicted diffusivity values are increased significantly. The effects of voids increase with the void volume fraction and are dependent on the voids’ location. If the fiber random distribution pattern is considered, it is found that the average values of predicted diffusivity decrease gradually with the increase in the number of oscillations.